Improving Student Learning Activeness Through the Numbered Head Together (NHT) Method in Class XI MIPA 3 Dance Learning at SMAN 30 Jakarta - Aprilia, Antika; Ojang Cahyadi; Selly Oktarini (Jurnal Pendidikan Tari, 2024)
The research aims to analyze the learning process of applying the Numbered Head Together (NHT) method to dance classification material to increase student learning activeness, which is the problem in this study. This problem leads to a lack of student activity in the learning process. In this study, the research method used was Classroom Action Research Classroom Action Research from Kurt Lewin with two cycles consisting of a series of steps consisting of four stages, namely planning, action, observation, and reflection in each cycle. Research activities took place from March to May 2023 at SMAN 30 Jakarta, Cempaka Putih, Central Jakarta. Data is collected through data collection techniques in the Form of questionnaires, observations, interviews and documentation. The results showed that the application of the NHT method to dance classification material could increase student learning activity based on the pre-cycle results of 57%, the first cycle increased by 78%, and the second cycle became 91%. The conclusion of this study is to use the Numbered Head Together (NHT) method on dance classification material to increase student learning activeness and experience an increase in each indicator of student learning activeness.